Pengaruh Model Pembelajaran Blended Learning Dalam Kebugaran Jasmani Terhadap Motivasi Belajar Siswa Kelas 12 Sekolah Ma Nurul Huda - Gery Mega Prastyo; Febi Kurniawan; Citra Resita (Jurnal Literasi Olahraga, 2020)
Abstract The problem in this research is how much the students learning motivation of class XII MANurul Huda. This study was to determine the Blended Learning model that affected student learningmotivation. The subjects in this study were all students of class XII MA Nurul Huda with 38respondents. The retrieval of data on this research using quantitative experimental methods. In thisstudy, the authors used a questionnaire method using data collection techniques with a test using alearning motivation questionnaire. The technique used in data collection in this study was using theOne-group Pretest-Post test Design. The results of this study show that student learning motivationhas increased after using the Blended Learning models which is seen from the pretest average score of184.16 with a posttest score of 212.34 this value shows that the final test has increased from the initialtest score and is strengthened by the average test value. one party is getting the value of Tcount6.010304 with Ttable 2.026, which means that H 0 is rejected and H 1 is accepted.Keywords: Blended Learning, physical fitness and learning motivation